The source field investigations [compact disc, unabridged] : the hidden science and lost civilizations behind the 2012 prophecies - Wilcock, David, 1973- (Brilliance Audio, 2011)
Based on a hugely popular Internet documentary, this exploration of historic signs and symbolism determines what the future holds for humanity come 2012.